2017
DOI: 10.1002/slct.201700851
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed Ni and Co Promoted MoS2  Catalysts with Magnetic Greigite as a Core: Performance and Stability in Hydrodesulfurization

Abstract: with greigite as the core were synthesized and compared to MoS 2 /Fe 3 O 4 for hydrodesulfurization (HDS). The composites with a greigite core were found to have higher hydrogenation (HYD) selectivity in HDS of dibenzothiophene (DBT) compared to the one with a magnetite core and showed higher stability during different cycles of DBT HDS test. Cobalt and Nickel as a promoter are uniformly dispersed over MoS 2 and decorated on the layer-structured MoS 2 . NiMoS/Fe 3 S 4 showed the highest activity in the hydrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Efficiency, as we might expect, was substantially increased with addition of amine compounds [ 34 ]. Yet, in contrast to its occlusion in mackinawite, molybdenum appears to be excluded from the inverse spinel, though Ni-bearing greigite can be coated with layered MoS 2 in the lab [ 247 ]. Dosed thus, Sharifvaghefi and Zheng showed that it can promote both hydrogenation and desulfurization reactions of, for example, dibenzothiophene (DBT, H 4 C 6 S C 6 H 4 ), while remaining stable [ 247 ].…”
Section: Iron Sulfides: the Supporting Castmentioning
confidence: 99%
“…Efficiency, as we might expect, was substantially increased with addition of amine compounds [ 34 ]. Yet, in contrast to its occlusion in mackinawite, molybdenum appears to be excluded from the inverse spinel, though Ni-bearing greigite can be coated with layered MoS 2 in the lab [ 247 ]. Dosed thus, Sharifvaghefi and Zheng showed that it can promote both hydrogenation and desulfurization reactions of, for example, dibenzothiophene (DBT, H 4 C 6 S C 6 H 4 ), while remaining stable [ 247 ].…”
Section: Iron Sulfides: the Supporting Castmentioning
confidence: 99%
“…After adding C16H36BrN, the surface of microspheres became smoother. The application of additives was favourable to fixation and nucleation, MoS2/Fe3S4, CoMoS/Fe3S4, NiMoS/Fe3S4 and MoS2/SiO2/Fe3O4 with CTAB and SDS were synthesized as additives [76,77]. The application of additive make the morphology of products become more homogeneous.…”
Section: Additivementioning
confidence: 99%
“…[33] Yet, in contrast to its occlusion in mackinawite, molybdenum appears to be excluded from the inverse spinel, though Ni-bearing greigite can be coated with layered MoS2 in the lab. [223] Dosed thus, Sharifvaghefi and Zheng show that it can, while remaining stable, promote both hydrogenation and desulfurization reactions of, for example, dibenzothiophene (DBT, H4C6S C6H4). [223] …”
Section: Greigite [Fe3s4]mentioning
confidence: 99%
“…[223] Dosed thus, Sharifvaghefi and Zheng show that it can, while remaining stable, promote both hydrogenation and desulfurization reactions of, for example, dibenzothiophene (DBT, H4C6S C6H4). [223] …”
Section: Greigite [Fe3s4]mentioning
confidence: 99%